Terapi Sufistik dalam Mengatasi Gangguan Kejiwaan di Griya Terapi Elkayyis Jatibarang Brebes - Zakiyatun Zakiyatun; Eva Latipah; Ismatul Izzah (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
A single Good spiritual and mental endurance will fortify themselves from problems with disturbances in themselves or what are commonly called mental disorders. Therefore, it is necessary to have good spiritual and mental endurance, in order to be able to fortify himself from these disorders. Research Methods using qualitative methods, namely research procedures that produce descriptive data. Data collection techniques using observation, documentation and interviews. This research took place at Griya Therapy Elkayyis in Jati Barang, Brebes, Central Java. This study describes the initial method, namely the general method by diagnosing mental disorders that occur starting from the background, symptoms, and therapy that will be carried out. The second step is to continue with the Sufistic therapy method, namely repentance, prayer, fasting, and dhikr. There are two indicators of a positive impact, namely, patients can recover or improve significantly and many new patients arrive. What happens in healing mental disorders at Elkayyis Therapy Center is the first is the lack of the number of therapists and the lack of scientific aspects.